2011
DOI: 10.1002/jcp.22722
|View full text |Cite
|
Sign up to set email alerts
|

Potential mechanism of interleukin‐8 production from lung cancer cells: An involvement of EGF–EGFR–PI3K–Akt–Erk pathway

Abstract: Tumor inflammatory microenvironment is considered to play the role in the sensitivity of tumor cells to therapies and prognosis of lung cancer patients. Interleukin-8 (IL-8) is one of critical chemo-attractants responsible for leukocyte recruitment, cancer proliferation, and angiogenesis. The present study aimed at investigating potential mechanism of IL-8 production from human non-small cell lung cancer (NSCLC) SPC-A1 cells. We initially found that EGF could directly stimulate IL-8 production, proliferation, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
81
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 106 publications
(85 citation statements)
references
References 30 publications
4
81
0
Order By: Relevance
“…Most studies to date have examined these pathways in isolation, but recently it is becoming clear that there is significant cross-talk between Akt and ERK pathways, which may function cooperatively in controlling cellular functions (31,35). Our findings shed light on the role of both pathways in driving p17-induced EC tube formation.…”
Section: Discussionmentioning
confidence: 70%
“…Most studies to date have examined these pathways in isolation, but recently it is becoming clear that there is significant cross-talk between Akt and ERK pathways, which may function cooperatively in controlling cellular functions (31,35). Our findings shed light on the role of both pathways in driving p17-induced EC tube formation.…”
Section: Discussionmentioning
confidence: 70%
“…In this study, we found that ANG II and AT1R were significantly increased in the tumor xenografts. ANG II has been shown to be pro-angiogenic through several potential mechanisms mainly via AT1R, including increasing expression of key growth factors, such as vascular endothelial growth factor (VEGF) and basic fibroblast growth factor, and increasing the production of matrix metalloproteinases to modulate new vessel formation [32].…”
Section: Discussionmentioning
confidence: 99%
“…Cell growth assay with CELL-IQ cell-culturing platform CELL-IQ was conducted as described (32). Briefly, the cell number was measured by the real-time cell monitoring system, using a Cell-IQ cell-culturing platform (Chip-Man Technologies).…”
Section: Acridine Orange Stainingmentioning
confidence: 99%